Chemical Composition and Phytochemical Screening of Ficus exasperata (Vahl) Leaf - Nimenibo-Uadia, Rachel (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Ficus exasperata Vahl leaf is a potent ethno-medicine in Ubiaja, Edo State, Nigeria, where it is used in treating diabetic persons. This study evaluates its chemical composition and screens its aqueous extract for phytochemicals using standard methods. Proximate analysis revealed a high level of ash (13.76) in g% dry weight suggestive of a reasonably good source of minerals. Others were crude fibre (12.50), crude protein (11.38), crude fat (2.10), while moisture content was 57.20 g% wet weight. Preliminary phytochemical screening showed the presence of tannins, flavonoids, alkaloids, anthraquinones, steroids and cardiac glycosides, though the frothing test failed to reveal the presence of saponins. The results support the folkloric use of Ficus exasperata leaf as a therapeutic agent and potential source of novel drugs.